Enhancing Income of Farmers Through Agribusiness Entrepreneurship - Kaundal, Babita; Vyas, Saurav; Singh, Sukhjinder (AMC Indian Journal of Entrepreneurship, 2022)
Developing countries like India rely heavily on agriculture to meet their demand for food, fodder, and fuel. In India, the agriculture sector supports 60% of the population for its livelihood and hence, plays an important role in its economic growth. It still remains the major contributor to India’s GDP besides employing 52% of its workforce. However, Indian agriculture is still characterized by traditional practices, the large number of small and marginal farmers with scattered fields, limited innovations, and lack of robust market modules. There is utmost need for the adaptation of new strategies and entrepreneurship in the agribusiness sector for the overall growth and economic development of the farming society in the country. A move from agriculture to agribusiness is critical for revitalizing Indian agriculture and making it more appealing and profitable. In the national economy, agripreneurship helps to generate jobs, income, reduce poverty, enhance nutrition, health, and overall food security as well as entrepreneurial opportunities in rural areas. Many of the remote areas are deprived of good infrastructure and technology which adversely affect the livelihood of farmers. A successful agripreneur should be able to manage scarce resources, establish market linkages, and have risk bearing ability. The present article focused on the need and role of entrepreneurship in the agribusiness sector, business models, and the role of policymaking in the successful translation of scientific knowledge for agribusiness development to enhance farmers’ income with appropriate environment.